Madrasah Accreditation Assistance at MTs Rodhatul Jannah, Palangka Raya - Dakir Dakir (Al-Qalam Institute, 2022)
Accreditation carried out by the government for madrasah isa form of public accountability carried out in an objective,fair, transparent, and comprehensive manner usinginstruments and criteria that refer to the National EducationStandards. This assistance aims to provide understanding tothe madrasah community in filling out and fulfillingMadrasah Accreditation to Improve the Quality of Educationat MTs Rodhatul Jannah, Palangka Raya. This assistance usesthe Participatory Rural Appraisal (PRA) technique. Theresults of assistance are carried out through activities; 1).Equalization of Perceptions about the importance ofaccreditation for improving the quality of madrasas, 2)Preparation of accreditation. The impact of mentoringactivities shows a positive direction, where there is a changein the mindset of the assisted subject related to madrasahaccreditation and an increase in the capacity of the madrasacommunity as evidenced by their success in filling out andcompleting the madrasah accreditation instrument.